2018
DOI: 10.1016/j.jacc.2017.11.028
|View full text |Cite|
|
Sign up to set email alerts
|

Autosomal Recessive Hypercholesterolemia

Abstract: Despite intensive treatment, LDL-C in ARH patients remains far from targets, and this translates into a poor long-term cardiovascular prognosis. Our data highlight the importance of an early diagnosis and treatment and confirm the fact that an effective treatment protocol for ARH is still lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 25 publications
3
17
2
Order By: Relevance
“…SVAS is a rare nding in ARH patients with aortic stenosis (20), which is typically seen in LDLR-HoFH. In agreement with previous studies (19,21), the clinical manifestation of our ARH patient mimicked the most severe form of genetic hypercholesterolemia, LDLR-HoFH: cutaneous…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…SVAS is a rare nding in ARH patients with aortic stenosis (20), which is typically seen in LDLR-HoFH. In agreement with previous studies (19,21), the clinical manifestation of our ARH patient mimicked the most severe form of genetic hypercholesterolemia, LDLR-HoFH: cutaneous…”
Section: Discussionsupporting
confidence: 92%
“…However, recently the nding of a worldwide collaboration project studying 52 ARH patients (28 females, 24 males) during a mean follow-up of 14.1 ± 7.3 years showed that incidence rate of ASCVD in the treated ARH patients was comparable to the patients with HoFH (19). Another similar phenotype with LDLR-HoFH is the risk of AVS, which occurs relatively often in patients with ARH (19). SVAS is a rare nding in ARH patients with aortic stenosis (20), which is typically seen in LDLR-HoFH.…”
Section: Discussionmentioning
confidence: 96%
“…It is caused by mutations in LDLRAP1, which codes for the low-density lipoprotein receptor adaptor protein-1. This protein plays a key role in the internalization of the LDL-R/LDL-C receptor complex, and loss-of-function mutations in the gene result in LDL-C remaining in circulation rather than being internalized by hepatocytes [37][38][39][40].…”
Section: Real-world Evidencementioning
confidence: 99%
“…Among the patients, high doses of statins and ezetimibe were recorded, and just over half of the patients were receiving apheresis. Six of the patients (11.5%) had received lomitapide [37]. Compared with other lipid lowering medication, patients receiving lomitapide had the greatest decreases in LDL-C levels, despite two of the patients stopping LA.…”
Section: Real-world Evidencementioning
confidence: 99%
See 1 more Smart Citation